(untitled) (World Bulletin of Social Sciences, 2023)
In the article, the form and content updates of children’s poetry are studied on the example of Abdurahman Akbar’s poems based on geometric figures, poems based on digital and word games. Also, the poems that are acceptable to be studied in children’s literature from a philosophical and educational point of view are analyzed on the basis of following and originality. In the analysis, the structural method was used in the study of the structure of poetic elements in the artistic text, and the formal method was used in the study of artistic, formal compositional elements as the most important theoreticalaesthetic category.